Early Career Effects of Entering the Labor Market During Higher Education Expansion - Johannes Goehausen; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2024)
We evaluate the labor market effects of an increasing supply of high-skilled labor, resulting from a higher education expansion at established German universities. Exploiting variation in exposure across regions and cohorts, we estimate early career effects for labor market entrants. We find that high-skilled wages decline initially, particularly in non-graduate jobs, but recover over the first five years of experience. Medium-skilled workers are barely affected, while low-skilled workers benefit from higher wage growth in non-routine-intensive jobs. We explain the dynamics of the effects by two countervailing mechanisms: immediate supply effects and gradual technology effects through increasing skilled labor demand.
Keywords: I23; I26; J31; R23; 330; higher education expansion; labor market entry; wages; regional labor markets